Peranan Paras-paras 3p0 dan 3p2terhadap Pekali Pengionan Sekunder dalam Nyahcas Townsend - Mat Yunus, W. Mahmood (1988)
The contribution of the 3Po and 3Po levels to the secondary ionization coefficient in a Townsend discharge are discussed. In the case of a research grade krypton gas sample, the theoretical values of 0 I a (the dominant process in the range Hlp < 50 volt cm- 1 to"-1 ) are in good agreement with the ex, perimental values of w I a. However, in the case of purified research grade krypton gas samples, it seems likely that only atoms in the 3P0 level contributed to the secondary ionization coefficient,